Tradisi Petik Laut dalam Komodifikasi Pariwisata Sendang Biru - Rahayuningtyas, Dyah; Siahaya, Thiovilia (Studi Budaya Nusantara, 2017)
Abstract Indonesia is a country that has a diversity both geographically and culturally. Through the diversity of Indonesia can develop resources in that is quite abundant as a tourist destination. One of the potential to be developed is the coastal area with all the cultures and communities, for example is "Petik Laut" tradition that is only owned by coastal communities. Although the development of tourism based on tradition and cultural values brings other consequences, namely making the tradition a part of tourism commodities. It takes certain strategies for a destination can be calculated as a tourist destination, one of which is to do the commodification, so as to attract tourists. Regardless of the positive or negative impacts, to date tourism is still a mainstay of Indonesia to improve the welfare, especially coastal communities.